Combining Artificial Neural Networks, Routine Health Records and Suicide Risk Estimation. (2018) - Banos, Marcos del Pozo; Travieso, Carlos M; Loxton, Kate; Petkov, Nicolai; Berridge, Damon; Lloyd, Keith; Jones, Caroline; Spencer, Sarah; John, Ann
No abstract available